BIODIVERSITY OF ARBUSCULAR MYCHORRIZAL FUNGI (AMF) ON POTATOS RHIZOSPHERE AND IT POTENTIAL AS BIOFERTILIZER - Yelianti, Upik; kasli, Kasli; Kasim, Musliar; Husin, Eti Farda (Lembaga Penelitian Universitas Negeri Padang, 2009)
AMF as the biofertilizer on several crops has been reported, but not so much the information about biodiversity of AMF on potatos rhizosphere and its potential to colonize that crop. The research about the biodiversity of AMF has been done in laboratorium Biology in Faculty of Agriculture of Andalas University and in laboratorium Biotecnology of Agriculture Faculty of Jambi University from November 2004 till April 2005. The sample of soil have been collected from rhizosphire of potatos plant in Alahan Panjang, West Sumatera, and then the AMF spore are isolated and identification based on morphology and size of spores. Inoculation of single and multi spores to potatos root to see the structure of colonization and percentage of colonization. The result of identification of AMF spores show that there are many kind of spores on rhizosphere of potatos plant and the spores are dominated by: Glomus, Acaulospora, Scutellospora, Gigaspora, and Enterophospora. Unfortunately, the inoculation of single spore has no good effect to the structure of colonization and the potatos plant not vigorous and easy to be severe of stem desease. But, inoculation with multi spores show that the tipe of colonization on potatos root have the coil hyphal and intracellular vesicular. The same result also indicated that colonization with active propagule (mycelium, spores, and infected root) have the coil hyphal and intracellular vesicular. The species of AMF that have the typical characteristic is assumed as Gigaspora sp.. Key words : AMF, potatos rhizosphere, biofertilizer